Landasan Pengembangan Kurikulum Pendidikan Islam: Landasan Filosofis, Sosiologis, dan Teknologis - Wafa, Ali; Sahri, Mat; Fajrin, Megawati (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
The aim of this research is to describe and analyze curriculum development based on philosophical, sociological and technological foundations in schools and madrasas. Curriculum development must pay attention to this foundation, because the curriculum is a guide for implementing learning. In developing the curriculum as a document for implementing learning in schools and madrasas, it must pay attention to Pancasila values ​​and traditional values ​​found in the surrounding community. This research uses a qualitative approach with library research. Data sources in this research, researchers used primary data sources and secondary data. Primary data sources include book reference studies, journal articles, the internet and other relevant ones. Meanwhile, secondary data sources in this research are other reference sources which still have relevance to the research focus, namely: the basis for developing the Islamic education curriculum: philosophical, sociological and technological. Then, content was analyzed from several primary and secondary data sources. The aim of this research is to reveal the philosophical, sociological and technological foundations for developing the Islamic education curriculum.